Implementasi Video Tutorial Pendidikan Karakter Pada Mata Kuiah Pendidikan Kewarganegaraan - Hudaidah Hudaidah; Amalia Ridho (Criksetra: Jurnal Pendidikan Sejarah, 2015)
This research activity is Developing Character Education Instructional Materials Based Video Tutorials That Used In Subjects Personality In MPK Sriwijaya University. This study is the development by using analysis of 8 steps referred to the development of Borg and Gall. Research conducted at the University of Sriwijaya MPK unit sample of 110 students study, consisting of 55 students in the experimental class and 55 students in the control class. Based on the results of this study can be summarized as follows: First, based character education teaching materials video tutorials which have been tested by an expert validation of materials and media, then tested on a one to one as much as 5 student sample, based on the results of these trials are conclusions video tutorial fit for use. Therefore it is diujicobkan video tutorials on subjects experimental class for Civic Education. Based on the validation test using a statistical test using the t test concluded that there are differences in the experimental class students' learning outcomes with the control class. Secondly, based on the mean compere test also showed that the learning outcomes obtained class mean ekspremen higher than the control class. Therefore this research-based teaching materials in addition to producing video tutorials for character education, proves also gives an influence on student learning outcomes.